A Multi‐Dimensional Framework of Organizational Innovation: A Systematic Review of the Literature - Crossan, Mary M.; Apaydin, Marina (Journal of Management Studies, 2010)
abstract This paper consolidates the state of academic research on innovation . Based on a systematic review of literature published over the past 27 years, we synthesize various research perspectives into a comprehensive multi‐dimensional framework of organizational innovation – linking leadership, innovation as a process, and innovation as an outcome. We also suggest measures of determinants of organizational innovation and present implications for both research and managerial practice.